2020
DOI: 10.1534/g3.120.401407
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Ceroid Lipofuscinosis in a Domestic Cat Associated with a DNA Sequence Variant That Creates a Premature Stop Codon inCLN6

Abstract: A neutered male domestic medium-haired cat presented at a veterinary neurology clinic at 20 months of age due to progressive neurological signs that included visual impairment, focal myoclonus, and frequent severe generalized seizures that were refractory to treatment with phenobarbital. Magnetic resonance imaging revealed diffuse global brain atrophy. Due to the severity and frequency of its seizures, the cat was euthanized at 22 months of age. Microscopic examination of the cerebellum, cerebral cortex and br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 79 publications
(128 reference statements)
2
14
0
Order By: Relevance
“…In consequence, the 132fsX mutant is likely to disturb the 239fsX mutant's structure, thereby nullifying its anti-aggregate activity. Recently, a homozygous mutation in cat CLN6 has been reported, where a guanine to adenine change (c.668G>A) creates a termination codon at Trp 223 (pTrp223Ter) (Katz et al 2020). Like human CLN6, cat CLN6 is also predicted to have seven transmembrane domains based on TMHMM, a membrane protein topology prediction program (http://www.cbs.dtu.dk/services/TMHMM/) and the Trp223 is situated in the fifth transmembrane domain (Supporting Fig.…”
Section: Removal Of Cln6's Luminal Tail Resulted In Insensitivity To the 132fsx Mutantmentioning
confidence: 99%
“…In consequence, the 132fsX mutant is likely to disturb the 239fsX mutant's structure, thereby nullifying its anti-aggregate activity. Recently, a homozygous mutation in cat CLN6 has been reported, where a guanine to adenine change (c.668G>A) creates a termination codon at Trp 223 (pTrp223Ter) (Katz et al 2020). Like human CLN6, cat CLN6 is also predicted to have seven transmembrane domains based on TMHMM, a membrane protein topology prediction program (http://www.cbs.dtu.dk/services/TMHMM/) and the Trp223 is situated in the fifth transmembrane domain (Supporting Fig.…”
Section: Removal Of Cln6's Luminal Tail Resulted In Insensitivity To the 132fsx Mutantmentioning
confidence: 99%
“…Table (5) showed the characteristics and laboratory findings of the 6 cases with NCL1. The clinical manifestations of the 6 cases with NCL1 showed that all the cases suffered from seizures, five out of 6 cases (83.3%) diagnosed with NCL1 had brain atrophy, regression of acquired milestones and optic problems, while 4 out of 6 cases (66.6%) had ataxia and microcephaly.…”
Section: Resultsmentioning
confidence: 99%
“…Table (5) showed the characteristics and laboratory findings of the 6 cases with NCL 2. The clinical manifestations of the 6 cases with NCL2 showed that all the cases suffered from seizures and regression of acquired milestones, five out of 6 cases (83.3%) diagnosed with NCL2 had brain atrophy, three out of 6 (50%) had ataxia and 2 out of 6 (33.3%) had optic problems, microcephaly was not evident in any of the diagnosed cases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent WGS studies in domestic cats have implicated causal variants in novel genes, including KIF3B variants causing retinal degeneration ( OMIA 002267-9685 ), UGDH causing disproportionate dwarfism ( OMIA 000187-9685 ), and GDF7 associated with another brain dysmorphology ( OMIA 000478-9685 ), all diseases with undiagnosed human patients [ 11 13 ]. New models for neuronal ceroid lipofuscinosis ( OMIA 001962-9685 ; OMIA 001443-9685 ) have further utilized WGS and now WES in domestic cats [ 14 , 15 ]. Intergenic structural variation (SV) and genome organization variation are becoming more recognized as keys to gene function.…”
mentioning
confidence: 99%